Diversity of seaweed-derived marine bacteria producing sulfated polysaccharide-degrading enzymes: Isolation, Screening, and Identification - Cao, Thi Thuy Hang; Tran, Nguyen Ha Vy; Nguyen, Thi Thuan; Vo, Thi Dieu Trang; Hoang, Hong Hanh; Ngo, Thi Duy Ngoc; Phan, Thi Hoai Trinh; Huynh, Hoang Nhu Khanh; Tran, Van Huynh; Tran, Thi Thanh Van; Pham, Duc Thinh (Vietnam Journal of Marine Science and Technology, 2025)
Marine bacteria associated with algae represent a valuable source of enzymes capable of degrading complex polysaccharides, such as fucoidan and ulvan. This study investigated bacteria isolated from 12 species of brown algae and 8 species of green algae, yielding 126 and 65 strains, respectively. Selective media supplemented with fucoidan or ulvan as the sole carbon source was employed to screen for enzymatic activity. The bacterial strains were characterized based on morphological features, and molecular identification was conducted through 16S rRNA sequencing. Several isolates demonstrated significant activity on fucoidan from Sargassum mcclurei and ulvan from Ulva fasciata. Phylogenetic analysis revealed a wide taxonomic range, with strains classified into the genera Alteromonas, Bacillus, Vibrio, Cobetia, and Delftia. This diversity underscores the metabolic adaptability of marine bacteria in degrading sulfated polysaccharides. The results provide insights into the enzymatic potential of marine bacteria for biotechnological applications, particularly in the conversion of algal biomass into bioactive compounds. These findings lay the foundation for further studies on enzyme characterization and industrial utilization of marine-derived polysaccharide-degrading bacteria.